Forces of Secularity in the Modern World: Volume 2 - Strehle, Stephen (Washington College Studies in Religion, Politics, and Culture Ser., 2020)
Stephen Strehle continues his detailed analysis of the secular forces that shape the modern world in this second and final volume to the study, offering a fresh perspective and solid philosophical, theological, and historical conclusions from his years of research.